2006
DOI: 10.1186/bf03351957
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the bottomside profile parameters over Wuhan with IRI-2001 for 1999–2004

Abstract: The diurnal, seasonal, and solar activity variations of the bottomside ionospheric profile parameters B0 and B1 are studied using electron density profiles measured over Wuhan (30.4 • N, 114.4• E) of China with a DGS-256 Digisonde during 1999-2004. Comparisons are made with the International Reference Ionosphere model (IRI-2001) using both the standard option (B0-Tab and B1-Tab) and the Gulyaeva's option (B0-Gul and B1-Gul). The results show that: (1) observed B0 has distinct diurnal and seasonal variations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The nighttime behavior (Fig. 4(c)) indicates somewhat "wave-like" pattern parallel to longitudinal behavior presented by Liu et al (2010) and seasonal variations of B o reported by Chen et al (2006) and Zhang et al (2008). Comparisons between Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The nighttime behavior (Fig. 4(c)) indicates somewhat "wave-like" pattern parallel to longitudinal behavior presented by Liu et al (2010) and seasonal variations of B o reported by Chen et al (2006) and Zhang et al (2008). Comparisons between Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The bottomside thickness parameters have also been studied by various researchers over the last three decades, including Booker (1977), Rawer et al (1985), Rawer (1988), Reinisch (2001), Stankov et al (2003), Zhang et al (2004), Chen et al (2006), Liu et al (2007), Nambala et al (2008), and Lee et al (2008). They have presented that the B0 shows distinct diurnal and seasonal variations, while B1 changes a little with seasons.…”
Section: Introductionmentioning
confidence: 96%
“…(1) this can then be converted into a model for B 0 . A much larger data base covering a wide range of global, seasonal, and solar cycle conditions was used by Bilitza et al (2000) for their B 0 and B 1 models that grew out of an IRI Task Comparisons with newer ionosonde data from a wide range of stations found marked shortcomings of both model options in accurately representing the observed seasonal and solar activity variations of B 0 and B 1 (Lee and Reinisch, 2006;Lee et al, 2008;Chen et al, 2006;Blanch et al, 2007;Sethi et al, 2009) and this was also confirmed with Millstone Hill incoherent scatter data by Lei et al (2004). The IRI team therefore strongly encouraged the development of new B 0 and B 1 models that would overcome these shortcomings and take advantage of the much increased data base.…”
Section: New Model For the Bottomside Electron Densitymentioning
confidence: 99%